Adult Type Xanthogranuloma: A Case Report - Sezer, Engin; Erkek, Emel; Sahin, Sedef; Cetin, Emel Dikicioglu (GALENOS YAYINCILIK, 2011)
Cutaneous xanthogranuloma is a dermatosis, clinically presenting as papules, nodules or plaques and histopathologically characterized by diffuse dermal infiltration of epithelioid cells with vesicular nuclei and conspicuous cytoplasm showing focal xanthomatous changes, and a mixed inflammation including eosinophils, neutrophils and lymphocytes. Although the disease is commonly observed in childhood, adult cases have also been reported and may cause confusion with various disorders histopathologically, including malignant melanoma. Herein, we report a case of adult type xanthogranuloma with reference to the literature.
Keywords: Xanthogranuloma; cutaneous xanthogranuloma; adult type